Administration of human chorionic gonadotropin at embryo transfer induced ovulation of a first-wave dominant follicle and increased progesterone and transfer pregnancy rates - L.D. Wallace; C.A. Breiner; A.R. Spell; J.A. Carter; G.C. Lamb; Jeffrey S. Stevenson; Ryan M. Breiner (Kansas Agricultural Experiment Station Research Reports, 2011)
Embryo transfer (ET) has become more widespread in recent years as a way to improve cattle genetics. According to the annual statistical survey of the American Embryo Transfer Association, more than 200,000 fresh and frozen bovine embryos were transferred in 2008. But despite advancements in reproductive technologies that have occurred since ET was commercialized in the 1970s, industrywide pregnancy rates are only 62.4 and 56.9% for fresh and frozen-thawed ET, respectively. Using ET helps avoid problems from failed fertilization; however, fertilization failure has been characterized as a relatively unimportant factor of pregnancy loss. Approximately 10% of pregnancy failures resulted from fertilization failure and another 10% from failed embryo development. Approximately 20 to 25% of the pregnancy loss in an ET program could be characterized as early embryonic loss.
Keywords: Kansas Agricultural Experiment Station contribution; no. 11-171-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1047; Cattlemen' s Day; 2011; Beef Cattle Research; 2011 is known as Cattlemen’s Day